Microbial L-malic acid production: History, current progress, and perspectives - Yongyan Xi; Feiyu Fan; Xueli Zhang (Green Carbon)
L-malic acid (L-MA) is an important intermediate in the tricarboxylic acid cycle and a crucial bulk chemical with various applications in the food, pharmaceutical, and chemical industries. With the rapid advancements in metabolic engineering technology and the global commitment toward fostering a green economy and sustainable development, the large-scale production of L-MA is gradually transitioning from conventional petroleum-based approaches to microbial fermentation. This comprehensive review aims to provide a thorough overview of the historical background and recent advancements in the microbial fermentation production of L-MA, encompassing an in-depth introduction to diverse biosynthetic pathways and host strains. Moreover, this review elucidates the challenges encountered in the industrialization of microbial fermentation production of L-MA, offering a summary of potential solutions and prospects for future research directions. The anticipated outcome of this review is to contribute valuable theoretical guidance toward promoting technological innovation in L-MA production.